The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.molimm.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-DNA antibody mediated catalysis is isotype dependent

Abstract: Anti-DNA antibodies are the serological hallmark of systemic lupus erythematosus, and participate in the pathogenesis of lupus nephritis by cross-reacting with multiple renal antigens. Previously, using a panel of murine anti-DNA IgGs that share identical variable regions but that differ in the constant regions, we demonstrated that the cross-reaction and renal pathogenicity of anti-DNA antibodies are isotype dependent. In this study, we investigated the catalytic potential of this anti-DNA antibody panel, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…It is unclear why the V L would be more likely to contain catalytic activity than the V H , but it is possible that antibodies with catalytic H chains have simply been infrequently identified and are thus under-represented in the literature and the PDB. We also note that the C H is known to have significant effects on the catalytic activities of at least two different antibodies (28,29,50). Thus, if the hydrolytic active site is present in the V L , this would imply that major inter-domain and inter-chain conformational changes can be propagated in immunoglobulins, a topic that warrants further investigation (61,62).…”
Section: Discussionmentioning
confidence: 85%
“…It is unclear why the V L would be more likely to contain catalytic activity than the V H , but it is possible that antibodies with catalytic H chains have simply been infrequently identified and are thus under-represented in the literature and the PDB. We also note that the C H is known to have significant effects on the catalytic activities of at least two different antibodies (28,29,50). Thus, if the hydrolytic active site is present in the V L , this would imply that major inter-domain and inter-chain conformational changes can be propagated in immunoglobulins, a topic that warrants further investigation (61,62).…”
Section: Discussionmentioning
confidence: 85%
“…As described previously (36), an ABI 4800 Analyzer (AB Science, Foster City, CA, USA) was used for such analysis. The ALW ( l -form or d -form) and KIR peptides (2 µg/ml) were mixed with anti-dsDNA IgG or control IgG (molar ratio = 1:5), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In an NMR study, the authors observed differences between the IgG subclasses with respect to their catalytic potential to cleave DNA, as well as the proteolytic activity toward a peptide mimic of the antigen. 137 While the 4 mAbs had the same primary cleavage sites for the peptide antigen, the catalytic efficiency differed among the subclasses. There was no correlation between the catalytic rates and the binding affinities to the peptide antigens.…”
Section: C-region Subclass Effects On V-region-identical Antibodiesmentioning
confidence: 99%